Contextual interference effects on volleyball serve acquisition: a controlled trial with physical-education majors - Qu, Luping; Xiao, Wenxian; Zhang, Shun; Wang, Ke; Li, Hui (Frontiers in Psychology, 2025)
To address limitations in previous domestic and international studies on “the effect of background interference on volleyball learning“, the present study selected 60 students majoring in physical education from the 2021 class at Qufu Normal University as experimental subjects to examine their skill acquisition. This study aimed to explore the differential effect of background interference on the learning of volleyball serving technique of students majoring in physical education. During an 8-week teaching experiment, the effects of three training modes, namely group block practice (low interference), mixed practice (medium interference), and random practice (high interference), on the learning effect of the serving technique of 60 physical education majors were compared. The results showed that (1) the block practice group performed optimally during the skill formation stage; (2) the random practice group had a significant advantage in the skill transfer test; and (3) the mixed practice group had the best effect in the long-term retention stage. The study provides empirical evidence for optimizing the teaching methods of volleyball techniques and has practical significance for the implementation of the policy of integration of sports and education.